Fresno County Young Lawyers Hopper Luncheon Keynoter California Supreme Court Associate Justice Malcolm Lucas - Watkins, Howard::::::::: (1985)
Barbara St. Louis, Donald Fischbach and Debra Kazanjian seated at head table